CURAHAN WAKTU KERJA WANITA DALAM USAHATANI HORTIKULTURA DAUN BAWANG DI DESA PINASUNGKULAN KECAMATAN MODOINDING - Lombogia, Alvandy; Rengkung, Leonardus Ricky; Tarore, Melissa Lady Gisela (Sam Ratulangi University, 2022)
This study aims to find out how much time women work in horticultural farming (leeks) in Pinasungkulan Village, Modoinding Sub-District. The data used in this study are primary data and secondary data. The sampling method was carried out by purposive sampling, namely the sample was taken intentionally. Data were analyzed using descriptive analysis and presented in tabular form. The results showed that women's working time in scallion horticulture farming in Pinasungkulan village was 339 hours. 12 hours were spent on tillage activities, 96 hours spent on planting activities, 84 hours spent on weeding activities, 30 hours spent on pest and disease control activities, 45 hours spent on fertilizing activities and 72 hours spent on harvesting activities.